Chorioangioma of Placenta: A Rare Placental Cause for Adverse Fetal Outcome. (13th June 2012) - Kodandapani, Sreelakshmi; Shreshta, Abha; Ramkumar, Vani; Rao, Lakshmi
Abstract : Chorioangioma is a benign angioma of placenta arising from chorionic tissue. Large chorioangioma has unfavourable effects on both mother and fetus. We describe a case with large chorioangioma that had a poor outcome on the fetus. We also reviewed the literature on prognostic factors affecting fetal outcome.